2021
DOI: 10.3390/jmse9020190
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Ecosystem-Level Trophic Cascade Effects Involving Gulf Menhaden (Brevoortia patronus) Triggered by the Deepwater Horizon Blowout

Abstract: Unprecedented recruitment of Gulf menhaden (Brevoortia patronus) followed the 2010 Deepwater Horizon blowout (DWH). The foregone consumption of Gulf menhaden, after their many predator species were killed by oiling, increased competition among menhaden for food, resulting in poor physiological conditions and low lipid content during 2011 and 2012. Menhaden sampled for length and weight measurements, beginning in 2011, exhibited the poorest condition around Barataria Bay, west of the Mississippi River, where re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In addition, the increase in biomass of age-0 gag following the 2005 red tide only occurred in model runs where all consumers were impacted by red tide, suggesting a trophic-driven compensatory response likely due to competition release. Several studies reported trophic cascades after the impact of stressors 59 , 97 99 . It is recognized that red tides impact the whole marine community 100 and therefore alter natural mortality and trophic interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the increase in biomass of age-0 gag following the 2005 red tide only occurred in model runs where all consumers were impacted by red tide, suggesting a trophic-driven compensatory response likely due to competition release. Several studies reported trophic cascades after the impact of stressors 59 , 97 99 . It is recognized that red tides impact the whole marine community 100 and therefore alter natural mortality and trophic interactions.…”
Section: Discussionmentioning
confidence: 99%